Support role undifferentiated connective tissue dysplasia in genital organ rolapse evolution - M. S. Selikhova; V. V. Skvortsov; G. V. Ershov; A. G. Ershov; G. I. Malyakin (Лечащий Врач, 2022)
One of the most significant risk factors for the formation  of internal  genital organs is connective  tissue diseases. The steady increase in the number of women suffering from pelvic organ prolapse has led to the fact that this pathology has become both a medical and socio-economic problem in many countries. At the same time, the data on the role of undifferentiated connective tissue dysplasias in the development of pelvic organ prolapse and in the formation of pelvic floor insufficiency and the possibility of using it to predict this pathology are contradictory.  To determine the relationship between the manifestation of undifferentiated connective tissue dysplasia and the development of pelvic organ prolapse, a retrospective analysis of 157 case histories of patients with genital prolapse was carried out. In 27,39% of patients, manifestations of connective tissue dysplasia were noted. In 39,53% of cases, a combination of the manifestation of undifferentiated  connective tissue dysplasias with birth traumatism was revealed. Severe forms of connective tissue dysplasia (varicose veins of the lower extremities, intestinal polyposis, mitral valve prolapse) were found in 16,28% of the number of cases with birth traumatism and pelvic organ prolapse, which required surgical correction  before pregnancy or after childbirth. Revealed in every third patient operated on for pelvic floor incompetence, undifferentiated connective tissue dysplasias allows us to consider it as a risk factor for pelvic organ prolapse, especially in combination with perineal trauma during childbirth. However, to assess the role and significance of connective tissue pathology in predicting the formation of prolapse and prolapse of the internal genital organs of the small pelvis in a woman, prospective randomized  studies are needed.